2017
DOI: 10.1016/j.dental.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Potential of electrospun chitosan fibers as a surface layer in functionally graded GTR membrane for periodontal regeneration

Abstract: The surface layer would act as seal to prevent junctional epithelium from falling into the defect site and hence maintain space for bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 68 publications
6
90
0
4
Order By: Relevance
“…Examples include incorporating chitosan into fibrin hydrogel for pulp regeneration, glass ionomer cement, scaffold, guided tissue regeneration (GTR) membrane, and in tissue conditioner for treating denture stomatitis. [20][21][22][23][24] The purpose of the present research was to develop chitosanbased denture adhesive that inhibits the adherence and growth of Candida species on denture base acrylic resin. Among the chitosan derivatives with different chemical characteristics that were tested against common oral Candida species, HMWC has the most effective fungicidal activity against both C albicans and many common NAC species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include incorporating chitosan into fibrin hydrogel for pulp regeneration, glass ionomer cement, scaffold, guided tissue regeneration (GTR) membrane, and in tissue conditioner for treating denture stomatitis. [20][21][22][23][24] The purpose of the present research was to develop chitosanbased denture adhesive that inhibits the adherence and growth of Candida species on denture base acrylic resin. Among the chitosan derivatives with different chemical characteristics that were tested against common oral Candida species, HMWC has the most effective fungicidal activity against both C albicans and many common NAC species.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Several applications in dentistry have been reported, including in endodontics, periodontics, and tissue engineering and as a drug delivery system. [18][19][20][21][22][23][24] Chitosan has broad-spectrum antimicrobial activity against bacteria and fungi by disrupting cell membranes and leading to intracellular leakage of ions and may inhibit deoxyribonucleic acid (DNA), ribonucleic acid (RNA), and protein synthesis. 16,25 Many chitosan derivatives exist, and their properties and antimicrobial activity vary with the molecular weight, degree of deacetylation, pH, and other factors.…”
mentioning
confidence: 99%
“…Qasim et al . produced aligned and random fibers for periodontal regeneration and showed that randomly oriented fibers promoted proliferation of osteoblasts . Stachewicz et al .…”
Section: Resultsmentioning
confidence: 99%
“…Microfabrication techniques have gained popularity in the creation of polymeric membranes with morphologies ranging in scale from micrometers to nanometers . Membranes produced through microfabrication techniques can potentially provide temporary support for different types of cells, such as fibroblasts, osteoblasts, neural cells, and others, and are applied in vascular grafts, artificial skin, drug delivery systems, shape memory devices, and scaffolds for tissue engineering …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chitosan appeared as a potential nanomaterial for dental uses due to its unique characteristic of antimicrobial agent being explored as a drug delivery system to ensure good public health dentistry. Therefore, antibiotics or other drugs used in oral diseses treatment can be loaded on chitosan nanoparticles having possible applications even in orthodontics as nano-materials deposited on mini-implants for a better osseointegration and prevention on microbial infections [17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%